Patient‐reported factors associated with the desire to continue taking sleep‐inducing drugs after hospital discharge: A survey of older adults. Issue 7 (10th June 2019) - Heinemann, Stephanie; Neukirchen, Freya; Nau, Roland; Hummers, Eva; Himmel, Wolfgang
Abstract: Purpose: To find out whether any prior experiences with sleep‐inducing drugs before hospitalization and positive experiences with these drugs during hospitalization influence a patient's wish to continue taking sleep‐inducing drugs after hospitalization. Methods: We surveyed older hospital patients about use of sleep‐inducing drugs before, during, and after hospitalization and compared these answers with their hospital chart using the kappa statistic. The association between the wish to continue these drugs after discharge and the perceived benefits, experience of side effects, and prior experience with sleep‐inducing drugs was determined by multivariable logistic regression. Results: Agreement between patient responses and the hospital file was high (κ = 0.7). Seventeen percent (83/483) of the participants reported prior experience before their hospital stay; 45% received a sleep‐inducing drug during hospitalization; 17% wished to continue taking them after discharge. Of the 400 patients who had no prior experience with sleep‐inducing drugs, 147 (37%) became first‐time users in the hospital, and 27% (40/147) of these wished to continue this medication after discharged. Strong predictors for this wish were the reduction of sleep onset problems (adjusted odds ratio, 6.26; 95% confidence interval, 2.38‐16.44) and any prior experience with sleep‐inducing drugs (4.08; 1.97‐8.48). Conclusions: Many older patients become first‐time users of sleep‐inducing drugs in the hospital. Especially the experience of sleep onset improvements influences the wish to continue sleep‐inducing drug use after discharge. Avoiding first‐time use should become a goal of hospital policy and be taken into account when weighing the benefits and risks of sleep‐inducing drugs.